Analisis dan Evaluasi Sistem Informasi Pengawasan Manejerial dan Akademik Sekolah (SIPMAS) Menggunakan Cobit Framework - Manja Purnasari; Nurhayati (STMIK Budi Darma, 2023)
The Education Department of Jambi City currently utilizes a School Managerial and Academic Information System (SIPMAS) to assist in monitoring the academic processes across all school levels under the jurisdiction of the Jambi City Education Department. SIPMAS is a system employed by individual teachers to upload teaching modules, instructional videos, syllabi and lesson plans, Student and Teacher Plans (TP and ATP), assessment guidelines, and learning evaluation results for each semester. To date, there has been no research conducted to monitor the system's performance, evaluate its usability, assess the system, and determine its alignment with the initial objectives set by the Jambi City Education Department for SIPMAS. Based on these considerations, a system evaluation was conducted using the 2019 version of the Control Objectives for Information and Associated Technology (COBIT) framework, with a focus on the Delivery, Service, Security (DSS) and Monitoring, Evaluate, Assess (MEA) domains. This evaluation aimed to measure the Process Capability Model (PCM) and conduct a gap analysis to assess the current maturity level of the SIPMAS system to meet the expected goals of the Jambi City Education Department. The research revealed capability level calculations for the selected objective domains, with the largest gaps observed in DSS02 (3.02), DSS03 (2.40), DSS04 (2.40), and MEA02 (3.10), all at level 1. This implies that the IT processes within the organization are starting to achieve their goals by implementing a series of activities, but there are still some shortcomings. These shortcomings can be characterized as the initial stages of an organized process towards goal achievement.